FAKTOR-FAKTOR YANG MEMPENGARUHI PERNIKAHAN USIA DINI ( Studi Kasus di Desa Pulau Birandang Kecamatan Kampar Timur Kabupaten Kampar) - Rio Arisandi; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The objectives of study were (1) to find out The factors influenced early marriage, (2) to find out society perspective on early marriage at the village of Pulau Birandang. The study focused on the age of first marriage with education background, knowledge, neighborhood, family system economy, culture social system, and religion. Early marriage means in the study was the marriage on the age of 21th. The conclusion made was on supported factors such as emotion, economy, education, education pattern and social. The study was descriptive qualitative using deep interview on one public figure of religion, 2 public figures, 1 staff of religious affair five respondents and 5 parents those did early marriage.The results of study that supported factors influenced early marriage at the village of Pulau Birandang the most was parent factor, because their children saw their parents got marriage early and the other said that his brother did early marriage too. So they see that early marriage is fun and they want to do it.The factor of group reference and environment factor has big influenced to create self-concept of young for early marriage, most respondent said the factor of group reference has the important effect, one of respondent said that their friend did early marriage so they wanted it too and it is also from their intention. One of informants said that in his place so many people did early marriage and it is not something strange for them.Keyword: early marriage, society perspective, the factors of early marriage